Cultural Walk- Rehabilitating the Image and Culture Eco-Tourism at Sri Tujoh Village Tumpat, Kelantan - Rozali, Muhammad Roslan Solahhudin (2018)
Kampung Sri Tujoh is a district of Tumpat, Kelantan. The physical area of Kampung Sri Tujoh is close to the Thai border. The village is very famous for its attraction as it is a charming and beautiful environment such as the attraction of the vast lagoon views and near the beach. Kampung Sri Tujoh also has a unique culture that is very active in fisheries such as fishermen, preserving fish in the lagoon and dry fish making. This area is potentially one of the attractions of culture that can attract tourists to come. This study shows that Kampung Sri Tujoh has its own unique strength and uniqueness.